Role of Common Addictive Habits on Hypovitaminosis D among Bangladeshi People - Rahman, AHM Habibur; Haque, Md Emdadul; Naznin, Lubna; Ahmed, Nasir Uddin (Medicine Today, 2019)
Introduction: Hypovitaminosis D is a silent but very devastating health issue throughout the world. Some common addictive habits in our country play important role on the issue. The objective of this study was to determine the role of common addictive habits on hypovitaminosis D among the clients attending specialized hospitals. Materials and Methods: This cross-sectional study was conducted among 264 respondents attended Armed Forces Institute of Pathology (AFIP), Dhaka Cantonment for estimation of 25(OH) D within the period of July 2017 to June 2018. Data were collected by face-to-face interview, reviewing with Vitamin D level of the participants from laboratory with the help of a semi-structured questionnaire and checklist respectively. Data were checked, and analyzed with the help of SPSS version 23. Results: Among the respondents, majority (68.56%) were female. The mean ±SD age of the respondents was 48.23 ± 14.05 years. The mean± SD level of 25(OH)D was 50.01± 29.93 nmol/L. Among the males, it was 50.86±28.61 nmo/L and 49.60±26.19 nmol/L among the female. The proportion hypovitaminosis D was 84.84% and a mare difference was found among male and female respondents (84.5% and 85.5% respectively. Smokers (43.88±13.01 nmol/L) were found with lower level of vitamin D than non-smokers (50.88±28.08 nmol/L) (p<0.05).The respondents having habit of chewing betel nut showed lowerlevel of 25 (OH) D than those does not practice that (51.63±18.07 Vs 46.12±13.01 mmol/L). Conclusion: The proportion of hypovitaminosis D was too high. Effective measure to be taken at all level to overcome the nutritional disorder. Medicine Today 2019 Vol.31(2): 89-92